Job Search and Unemployment Duration in The Metropolitan Area of Cali: a Count for The Second Quarters of 2009 and 2010 - Jiménez, Diana Marcela (Sociedad y Economía, 2012)
Employed and unemployed mainly used the informal channels of job search to find job. Your choice is consistent with these strategies are the most efficient, to relate to lower unemployment durations, and the most effective in terms of allowing a jobseeker finding a job. With information of GEIH, for the metropolitan area of Cali in the seconds quarters of 2009 and 2010, found that the formal channels of search job are less efficient that the informal channel but it is most efficient that the moderate informal channel.